APPROXIMATION OF (ψ, β)-DIFFERENTIABLE FUNCTIONS DEFINED ON THE REAL AXIS BY WEIERSTRASS OPERATORS - Кальчук, Інна Володимирівна; Kalchuk, Inna V. (Springer New York Consultants Bureau, 2007)
We obtain asymptotic equalities for the upper bounds of approximations by Weierstrass operators on the functional classes C^{\psi}_{\beta,infty} and L^{\psi}_{\beta,1} in the metrics of the spaces C and L, respectively
Наближення (ψ, β) -диференційовних функцій, заданих на дійсній осі, операторами Вейєрштрасса